Health behaviours of 17- to 19-year olds in North East England: assessing adherence to current recommendations for young people at the adolescent-adult boundary. - Basterfield, L; Rowland, M; Rigg, R; Reilly, J J; Janssen, X; Pearce, M S; Evans, E H; Adamson, A J (Perspectives in Public Health)
Aims: Late adolescence/young adulthood represents a transition to independence, with increasing control over health behaviours (hB). however, hB data of late adolescents are often reported in wide and inconsistent age brackets, making comparisons with age-targeted guidelines difficult. We aimed to characterise important hB (body composition, physical activity (pA), diet) of late adolescents from North east england. Methods: A total of 145 17- to 19-year olds from the Gateshead Millennium Study birth cohort participated in 2017 to 2018. Measurements including height, weight, body fat, accelerometer-measured pA and sedentary behaviour, and 24-hour dietary recall were taken. Comparisons with current global age-appropriate recommendations were made for four variables: (1) 60 min moderate-vigorous intensity pA (MVpA)/day (age 17 years old) or 150 min MVpA/week (18- to 19-years old); (2) body fat (<25% for males, <30% for females); (3) free sugars <5% total energy intake; (4) five portions fruit and/or vegetables/day. Results: Most recommendations were not met: MVpA averaged 37 min/day, 20% of 17-year olds met 60 min/d, and 55% of 18- to 19-year olds met 150 min/week. About 26.5% of participants had excess body fat. Daily fruit/ vegetable consumption was 2.7 portions; 12% consumed ‘5-a-day’ portions of fruit and/or vegetables, 13.5% consumed <5% energy from free sugars. together, 43% of participants met 0/4, 44% met 1/4%, and 0% met 4/4 ageappropriate health recommendations. Conclusion: these novel empirical data reveal concerning hB in this population of late adolescents, suggesting targeted health messaging to improve hB is needed.
Keywords: physical activity; public health; obesity